Hubungan Keberadaan Kedua Orang Tua Di Rumah Bersama Siswa terhadap Motivasi Belajar dan Prestasi Akademik - Rachma Tullah, Rosna Andini; Crismono, Prima Cristi; Ilyas, Muhammad (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2023)
Starting with an incident that arose, there were two students who were twins but different. One of them has traits that are common among children on his age. Meanwhile, the other has a strength that is not generally possessed by children on his age, this student can know which of his interlocutors he can control and which he cannot control. The aim of this research is specifically for parents, so that they better understand how the presence of both parents at home with their child on their child's growth and development and future, such as motivation to learn in children so they get good academic achievement results for their future. The method used is quantitative research with Correlation/Relationship Test analysis techniques assisted by the SPSS 25 application, with a significance level of 5%, worth 0.367. The results of variable (x) and variable (y1) are the results of the questionnaire, while variable (y2) is the odd semester class IV-A. From the calculations, the result was that the first hypothesis, (H1)=x→ y1, the value obtained was 0.753, which could be accumulated in the high and low correlation category, including the "High" category. And the second hypothesis, (H2)=x→ y2 can be concluded, the value obtained is 0.549, which can be accumulated in the category of high and low correlation results including in the "Medium" category. It was concluded that the presence of both parents at home with students had a very significant relationship between learning motivation and students' academic achievement at school. This means that the more intensive the presence of both parents at home with the student will make better the student's learning motivation and also the student's academic achievement Keywords:Parents; Learning motivation; Academic achievement